FUNCTIONING VAGAL PARAGANGLIOMA - Lim, LA; Rajoo, Subashini (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Paragangliomas (PGLs) are rare neuroendocrine tumors arising from sympathetic or parasympathetic paraganglia, which can be sporadic or familial. Sympathetic PGLs are almost always functional (clinically active) while parasympathetic PGLs are usually not. Parasympathetic PGLs usually arise in four distinct areas: carotid body, vagus, middle ear, and larynx. Herein, we report a case of functional vagal paraganglioma and discuss its management. RESULTS A 49-year-old female presented with a painless neck swelling, which was gradually increasing in size over the past 4 years. She sought medical advice after experiencing episodic headache along with palpitation and 10kg weight loss over a 2-month period. She had a noticeable right sided neck swelling, and labile blood pressure. Further evaluation revealed elevated 24 hour urine noradrenaline and an metaiodobenzylguanidine (MIBG)-avid right neck mass. Following a diagnosis of functioning neck paraganglioma, phenoxybenzamine and carvedilol were initiated two weeks prior to surgery. She underwent embolization followed a day later by surgical excision of the tumor with vagus nerve reconstruction. Intraoperatively, a short period of sodium nitroprusside infusion was required during manipulation of the tumor. Postoperatively, a brief period of inotropic support was required. Histologic examination of the excised mass revealed a paraganglioma with a low proliferative index (Ki 67 <5%). She was well and normotensive upon discharge. CONCLUSION Paraganglioma is a rare and curable cause of hypertension. Preoperative preparation with alpha-blocking with or without beta-blocking agents together with volume expansion are crucial before surgical resection. This case highlighted the importance of a multidisciplinary team involvement in every aspect of the patient’s care in order to have an adequate decision-making process.